2006
DOI: 10.1097/01.qai.0000245887.58886.ac
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Benefit From a Long-Term Antiretroviral Adherence Intervention

Abstract: This large randomized clinical trial demonstrated that interpersonal structured adherence support was associated with improved long-term medication adherence and virologic and immunologic HIV outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
87
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 34 publications
5
87
0
1
Order By: Relevance
“…Results of these prior studies are inconclusive. For example, Mannheimer and colleagues (18) found that patients assigned to a medication manager-who was often a research nurse-had a higher mean increase in CD4 count by an average of 22.4 at the end of 36 months, which is very consistent with our findings. Viral load differences were not statistically significant in their study.…”
Section: Discussionsupporting
confidence: 82%
“…Results of these prior studies are inconclusive. For example, Mannheimer and colleagues (18) found that patients assigned to a medication manager-who was often a research nurse-had a higher mean increase in CD4 count by an average of 22.4 at the end of 36 months, which is very consistent with our findings. Viral load differences were not statistically significant in their study.…”
Section: Discussionsupporting
confidence: 82%
“…Studies demonstrated that HIV-infected patients who received EI had obtained significant improvement in adherence [20][21][22][23][24]. Our study results also show similar positive significant association of greater than 95% of adherence outcomes to HAART in ICG patients (67.5%, p<0.001) after having received EIs on adherence counseling in comparison with SCG.…”
Section: Discussionsupporting
confidence: 78%
“…For example, given that forgetting to take ART has been reported to be one of the most commonly stated adherence barriers, [12][13][14][15][16] many studies have examined the use of reminder devices in improving adherence. [17][18][19][20] However, most have not revealed clinically significant changes in adherence. Studies have reported other adherence barriers, including feeling depressed or overwhelmed, fear of disclosure, sleeping through a dose, substance use, regimen complexity, not having medication, change in daily routine, and not wanting to be reminded of HIV infection.…”
Section: Introductionmentioning
confidence: 99%